O2-dependent large electron flow functioned as an electron sink, replacing the steady-state electron flux in photosynthesis in the cyanobacterium Synechocystis sp. PCC 6803, but not in the cyanobacterium Synechococcus sp. PCC 7942. Issue 3 (4th March 2014) - Hayashi, Ryosuke; Shimakawa, Ginga; Shaku, Keiichiro; Shimizu, Satoko; Akimoto, Seiji; Yamamoto, Hiroshi; Amako, Katsumi; Sugimoto, Toshio; Tamoi, Masahiro; Makino, Amane; Miyake, Chikahiro
Abstract: To determine whether alternative electron flow (AEF) can replace the photosynthetic electron flow in cyanobacteria, we used an open O2 -electrode system to monitor O2 -exchange over a long period. In air-grown Synechocystis sp. PCC 6803 (S. 6803(WT)), the quantum yield of PSII, Y(II), held even after photosynthesis was suppressed by CO2 shortage. The S. 6803 mutant, deficient in flavodiiron (FLV) proteins 1 and 3, showed the same phenotype as S. 6803(WT). In contrast, Y(II) decreased in Synechococcus sp. PCC 7942 (S. 7942). These results suggest that AEF functioned as the Y(II) in S. 6803 and replaced the photosynthetic electron flux. In contrast, the activity of AEF in S. 7942 was lower. The affinity of AEF for O2 in S. 6803 did not correspond to those of FLVs in bacteria or terminal oxidases in respiration. AEF might be driven by photorespiration. Graphical abstract: : Cyanobacterial species dependence of alternative electron flow to replace the electron Flux in Photosynthesis: a, Synechocystis (S. 6803); b, Synechococcus (S. 7942).